Contaminated Ambu-Bag Associated Hospital-Acquired Infection with Pseudomonas aeruginosa in an Intensive Care Unit (Annals of Medical Research, 2021)
None
Keywords: Hospital-Acquired Infections; Ambu-Bag; Intensive Care Unit, emPseudomonas aeruginosa/em